Analisis Budaya Konsumerisme dan Gaya Hidup Dikalangan Remaja Akibat Pengaruh Media Sosial di Kota Tanjungpinang - Monica, Sely; Prilda Siagian, Naomi; Rokhim, Atika (Jurnal Indonesia Sosial Sains, 2022)
Community life in this era increases the needs of human life. The more needs that are needed, the more the demands of life style. In this modern era, lifestyle is the hallmark of a modern world. Moreover, in the midst of the development of social media that can improve lifestyles, it will have a negative impact if consumptive behavior is not carried out according to needs. This study aims to describe the lifestyle of teenagers. The targets in this study were taken from several teenagers in the city of Tanjung Pinang. The sociological study used is a theoretical study from Jean Baudrillard on lifestyle, symbol consumption, and studies on social and adolescent motives. The research uses a qualitative descriptive method, which aims to get a clear and detailed picture of the problem to be studied by studying as much as possible an individual, a group or an event that occurs in the field.